Profile of SARS-CoV-2 - Heinz, Franz X. (Wien Klin Wochenschr, 2020)
The recent emergence of a new coronavirus (severe acute respiratory syndrome coronavirus‑2, SARS-CoV-2) that is transmitted efficiently among humans and can result in serious disease and/or death has become a global threat to public health and economy. In this article, we describe some of the most important characteristics of this new virus (including gaps in our understanding) and provide a perspective of ongoing activities for developing virus-specific countermeasures, such as vaccines and antiviral drugs.